Sistema Web para el control de procesos internos en la Junta de Riego y Drenaje del Cantón Babahoyo - Lindao Uchubanda, Wander Ley (2018)
At present, computer systems have evolved, in such a way that a company requires a technological infrastructure which provides a better service in each of its processes. The web systems were created to be hosted on a server on the Internet or on an intranet. Web applications have a very similar to the web pages we see normally, web systems have very powerful features that provide answers to specific cases. These web systems can be manipulated in any web browser (Chrome, Firefox, Internet Explorer, etc.) and it does not matter what operating system you have. To use web applications, it is not necessary to install them on each computer since users connect to the server where the system is hosted. The web systems work together with the database that allows them to process the information to be visualized by the user. The technology nowadays is a tool very used in the companies to be able to streamline the activities of the processes, which allows them to improve the flow of information since it needs to be stored and processed at any time. The sector of CEDEGE of the Babahoyo canton is a distinctly agricultural area, there are many varieties of crops such as corn, soybeans and rice which are necessary products for consumption in society. The product with the highest production is rice because the project has an irrigation and drainage system for users who are in the system and for those who do not appear in the system they are also provided with the service.